Reaction Mechanism Optimization of Solid‐State Li–S Batteries with a PEO‐Based Electrolyte. (13th May 2020) - Fang, Ruyi; Xu, Henghui; Xu, Biyi; Li, Xinyu; Li, Yutao; Goodenough, John B.
Abstract: The shuttle effect of long‐chain polysulfides (Li2 S n, n = 4–8) from the multistep reactions reduces the cycling life of solid‐state lithium–sulfur (Li–S) batteries with a poly(ethylene oxide) (PEO)‐based solid polymer electrolyte (SPE). Moreover, the ambiguous reaction mechanism of polysulfides in an SPE also limits the development of high‐performance solid‐state Li–S batteries. Here, a solid‐state Li–S cell with a much‐improved cycling performance is reported by coating the sulfur cathode with a layer of polyvinylidene fluoride (PVDF), which not only suppresses the formation of soluble polysulfides, but also changes the reaction mechanism of the sulfur from a multistep "solid–liquid–solid" reaction to a single‐step "solid–solid" reaction. These results show that long‐chain polysulfides are insoluble and unstable in PVDF polymers with a low solvent property, which facilitates the direct transformation of elemental sulfur to solid Li2 S2 /Li2 S without the formation of intermediary products. However, the strong PEO–Li2 S n ( n = 4–8) attraction causes a dissolution of polysulfides in PEO. The introduction of a polymer with a low solvent property in the sulfur cathode would be promising for the development of solid‐state Li–S batteries with a long cycling life. Abstract : Coating S/C cathodes with polyvinylidene fluoride changes the reaction mechanism of the solid‐state lithium–sulfur (Li–S) cell with a poly(ethylene oxide) (PEO)‐based solid electrolyte from a multistep "solid–liquid–solid" to a one‐step "solid–solid" reaction. The polyvinylidene fluoride suppresses the formation of soluble polysulfides and significantly improves the cycling stability of the cell.